Acellular nerve graft re-seeded by Schwann cells migrating from the nerve stump can stimulate spinal motoneurons for functional reinnervation of the rat muscle - Haninec, P; Dubový, P; Houst'ava, L; Stejskal, L (Annals of anatomy, 2000)
The acellular nerve graft was utilised to restore a functional reinnervation of the biceps brachii muscle from the motoneuron pool of the cervical spinal cord. The musculocutaneous nerve stump was sutured to an acellular nerve graft, the opposite end of which was inserted into the cervical spinal cord cranial to the avulsed C5 ventral root. The acellular nerve graft was repopulated by Schwann cells heavily immunostained for NGFr within 90 days. The Schwann cells migrating from the nerve stump reached the spinal cord grey matter, where they stimulated the motoneurons to send axonal sprouts. The functional reinnervation of the biceps brachii muscle was assessed by means of the behavioural (grooming) test and EMG, the presence of myelinated and unmyelinated axons was demonstrated by light and electron microscopy. The axonal reconnection of the musculocutaneous nerve stump was verified by horseradish peroxidase retrograde labelling of the spinal motoneurons. Moreover, the motoneurons on the operated side of the C5 spinal segment displayed increased immunostaining for GAP-43 in comparison to the contralateral side, whereas the pattern of AChE histochemical reaction was similar on both the operated and contralateral side, of the C5 segment 150 days after acellular graft implantation. The regenerated axons bridged a 4-cm long originally acellular nerve graft to reach and reinnervate the biceps brachii muscle. The reinnervation of the neuromuscular junctions was morphologically determined by immunofluorescence for neurofilaments. The number of myelinated axons in the acellular nerve graft was significantly higher than those growing over the cellular graft, but their diameter was smaller. The results of experiments presented here demonstrate functional recovery of the biceps muscle reinnervation through the acellular nerve graft repopulated by migrating Schwann cells. The process of reinnervation by acellular nerve graft is however delayed and worse in comparison with the cellular graft.
Keywords: denervace svalu; Schwannovy buňky; Spinal Cord; míšní kořeny; Muscle Denervation; Schwann Cells; Female; mícha; krysa rodu Rattus; Peripheral Nerves; zvířata; Nerve Regeneration; péče o zevnějšek u zvířat; Electromyography; regenerace nervu; potkani Wistar; kosterní svaly; Spinal Nerve Roots; ženské pohlaví; pohyb buněk; Rats, Wistar; Grooming; Muscle, Skeletal; Cell Movement; Rats; Animals; periferní nervy; elektromyografie